Workplace cyberbullying: a systematic literature review on its definition, theories, and the role of HRD - Sanjeeva Kumar Pothuganti (Cogent Business & Management, 2024)
Workplace cyberbullying has garnered significant attention, although the most focus has centred on its effects on work, related stressors, and consequences. Workplace cyberbullying has a detrimental impact on employees and undermines the effectiveness of information systems. It is crucial to review the existing body of work to understand the dynamics of cyberbullying in modern digital workplaces. The literature study has focused on synthesizing existing literature to define workplace cyberbullying accurately. It aims to uncover underlying theories and their implications on individuals affected by cyberbullying. The study examines the significance of researching workplace cyberbullying and how existing evidence informs our understanding. Lastly, it explores the critical role of Human Resource Development (HRD) in addressing and mitigating cyberbullying incidents, emphasizing their importance in this context. By conducting an integrated assessment of 52 empirical research works, this research can provide valuable insights into the frequency, causes, and consequences of cyberbullying, allowing organizations to establish policies and measures to protect their employees and promote a positive workplace culture. This review will enable the research community to grasp the concept of workplace cyberbullying and assess the current state of research in the field.
Keywords: 650; workplace technology; workplace-cyberbullying; Review; Digital work; electronic Bullying; information and communication technologies